Identifying risk factors and evaluating therapeutic interventions for anastomotic recurrence in postoperative esophageal squamous cell carcinoma - Tiantian Cui; Huajian Chen; Min Fan; Wei Huang; Xiaodong Liu (BMC Cancer)
Abstract Purpose This investigation delineates the differential impact of recurrence patterns—specifically, anastomotic recurrence (AR) and lymph node recurrence (LNR)—on the survival outcomes of patients with esophageal squamous cell carcinoma (ESCC). Additionally, it assesses the therapeutic efficacy of adjuvant radiotherapy in modifying these postoperative recurrence dynamics to inform optimized clinical management. Methods and materials A retrospective cohort analysis was conducted on 434 patients who developed recurrent ESCC following radical surgery at Shandong Cancer Hospital, from July 2018 through December 2022. Comprehensive clinical data were analyzed using logistic and Cox proportional hazards regression models to elucidate the risk factors associated with AR and LNR. Results Of the patients analyzed, 118 exhibited AR post-surgery. Multivariate logistic regression identified advanced N stage and the presence of LNR as predominant risk factors influencing recurrence. Survival analysis, employing Kaplan–Meier estimates, demonstrated a median survival time (MST) of 21 months (range: 1.6–146.1 months) for patients with AR. In patients experiencing LNR, Cox regression analyses revealed tumor location and the application of adjuvant radiotherapy as critical determinants of survival outcomes. Significantly, adjuvant radiotherapy markedly reduced the incidence of LNR, thereby attenuating overall recurrence rates. Conclusions Postoperative recurrence significantly compromises survival in ESCC, underscoring the critical need for precise risk stratification and proactive management. This study substantiates the prognostic significance of adjuvant radiotherapy in reducing recurrence, providing pivotal insights for tailoring treatment protocols to enhance patient prognoses in ESCC.